Having "Banks Play Along": Varieties of State-Bank Coordination and State-Guaranteed Credit Programs During the Covid-19 Crisis - Elsa Massoc (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
In times of crisis, governments have strong incentives to influence banks' credit allocation because the survival of the economy depends on it. How do governments make banks "play along"? This paper focuses on the state-guaranteed credit programs (SGCPs) that have been implemented in Europe to help firms survive the COVID 19 crisis. Governments' capacity to save the economy depends on banks' capacity to grant credit to struggling firms (which they would not be inclined to do spontaneously in the context of a global pandemic). All governments thus face the same challenge: How do they make sure that state guaranteed loans reach their desired target and on what terms? Based on a comparative analysis of the elaboration and implementation of SGCPs in France and Germany, this paper shows that historically-rooted institutionalized modes of coordination between state and bank actors have largely shaped the terms of the SGCPs in these two countries.
urn:nbn:de:hebis:30:3-616453
Keywords: 330; state; banks; infrastructural power; institutions; COVID-19